MANFAAT REFORMASI AGRARIA BAGI PEMENUHANHAK-HAK ASASI PETANI - Pristi Suhendro L (Universitas Negeri Medan, 2013)
After the end of the Cold War caused the collapse of the socialist countries, the ideas and policies ofliberalization, privatization and modernization became the dominant current of thought.The rise of theneo-liberals have created an atmosphere that was not conducive to the idea of Agrarian Reform (RA).Anexample is the rampant land disputes that human casualties.The dispute occurred in almost all areasand involves almost all sectors.Based on reports BPKPA (2000), at least 1742 cases recorded as landdisputes in Indonesia, the largest in the 25 provinces.Then the dispute was followed by 12 cases ofabduction, 24 cases of murder, 39 cases of shootings, 151 terror cases, 163 cases of torture, 212 cases ofintimidation, and 763 arrests.Agrarian condition at some time in fact a product of the operation of fourinteracting factors, namely: (a) historical legacy, (b) internal dynamics, (c) government interventionthrough its policies, and (d) external intervention such as, large private companies both domestic andforeign, the movement of the